Increasing Community Knowledge through Larvitrap’s Making Training as an Effort to Prevent Dengue Hemorrhagic Fever (DHF) in Rowosari Village, Semarang - Mochamad Rizal Maulana; Eko Naning Sofyanita; Ichsan Hadipranoto (CV Firmos, 2024)
Dengue fever is a disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. The emergence of this disease is related to environmental conditions including weather and community behavior. The purpose of this activity is to increase community knowledge and skills in efforts to prevent and control dengue hemorrhagic fever (DHF). The method used was socialization and training on larvitrap making for the Rowosari village community, Semarang. The participants were 50 men and women with an average age of 50 years with various educational backgrounds who live in the Rowosari Village area, Semarang City. The results of this activity showed an increase in knowledge through socialization and training. Paired sample t-test on the pre-test and post-test scores showed a p-value of 0.000 or less than 0.05, which means that there is a difference in community knowledge before and after the socialization and training. The conclusion of this activity is that the training on prevention and control of DHF through Larvitrap making is effective in increasing the knowledge and skills of the community in Rowosari Village, Tembalang Subdistrict, Semarang City.